Molecular phylogenies of Blastocystis sp. isolates from different hosts: Identification of subtypes, implication for pathogenicity and zoonosis / Dr. Tengku Shahrul Anuar Tengku Ahmad Basri and Nabilah Amelia Mohammad - Tengku Ahmad Basri, Tengku Shahrul Anuar; Mohammad, Nabilah Amelia (Research Management Institute (RMI), 2017)
Blastocystis sp. is a single-celled enteric parasite that is commonly found in humans and a variety of animals, including primates, other mammals, birds, reptiles and amphibians. This parasite exists in various morphologies such as vacuolar, granular, amoeboid and cyst forms. The water-resistant infective cyst represents the transmissible stage of the parasite, whereas the large amoeboid form has been suggested as being associated with pathogenicity (Rajamanikam & Suresh, 2013). The distribution of the parasite is worldwide and the prevalence in human stool samples ranges from 7% to 20% in developed countries to 30% to 60% in rural areas in developing countries. The high prevalence has been linked to poor hygiene practices, exposure to animals and consumption of contaminated food or water since the fecal-oral route is considered to be the main mode of transmission of this parasite. Indeed, a higher risk of infection has been found in humans with close animal contact (food and animal handlers) reinforcing the zoonotic nature of the parasite (Anuar, Ghani, Azreen, Salleh, & Moktar, 2013). A consensus terminology for subtypes (ST) of Blastocystis sp. was developed on the basis of small subunit ribosomal RNA (SSU rRNA) gene analysis and seventeen subtypes were established and designated as ST1 to ST17 (Nithyamathi, Chandramathi, & Kumar, 2016). Blastocystis sp. has low host specificity and is considered a potential zoonotic pathogen because infections in humans has been associated with contacting primates, pigs and poultry (Yoshikawa et al., 2016). ST1 and ST2 were observed shared between children and domestic pigr (Yoshikawa et al., 2016)…